(untitled) (International Journal of Engineering and Computer Science, 2014)
Hadoop is a “flexible and available architecture for large scale computation and data processing on a network of commodity hardware”it is processingtechnology for large scale applications. Nowadays unstructured data is growing at faster rate. Big data generated daily from social media, sensor used to gather climate information, digital picture purchased transactions records and many more. Ultimately there need to process Multi Petabyte Datasets efficiently. Failure in datasets is expected, rather than exceptional. The number of nodes in cluster is not constant. The Hadoop platform was designed to solve such problems as it provides application for operational and analytics. Today Hadoop is fastest growing technology provides advantage for business across industries in world.